(untitled) (Journal of the College of Education for Women, 2019)
The research aims to identify the current (after the readings in the collection of foreignstudents to the geographical material) To achieve this, the researcher developed the followingnull hypothesis:No statistically significant differences at the level of (0.05) between the average scores whoare studying the use of article readings and the average external degree students who arestudying material in the traditional manner of collection.The researcher has chosen Qsidia middle school Amma, which includes six divisions forGrade average, randomly selected Division (a) to represent the control group, whilerepresenting the Division of (c) the experimental group and reached the research sample (44)student, by (22) student in each division and was rewarded with the Find the two sets ofstudents in statistical variables chronological age calculated in months, and degrees ofgeographical material in half, and testing prior experience, academic fraud and the father andmother.After determining the researcher of scientific material, of Chapter III and IV of the bookGeography of the Arab world, has formulated a researcher targets behavioral numbered (93)the target behavior and plans for teaching the two groups, the achievement test and presentedto a group of specialists in the light of their views, conducted the necessary adjustments andhas become the plans ready for implementation and for the purpose of measuring collection ofstudents two sets of research in the subjects studied by the researcher herself, has prepared atest Thilaa Badia consisted of (50), paragraph a test of the type of multiple choice, offered thegroup Almt_khasan to verify the veracity of the test and after analyzing the results of answersto students of the sample and processed statistically found that the paragraphs of the test areall valid To calculate the stability of the test method was used retail midterm treated their datausing the Pearson correlation coefficient, which Heh equation Spearman - Brown reached(0.69), a coefficient of stability is good, and after the end of the experiment was appliedachievement test the post to students two sets of research and after analyzing the results ofanswers to students and processed statistically using test Altaúa for two independent samplesproved the existence of significant differences statistically between the average degree ofachievement of students of the experimental group which studied the material geographicalreadings of Foreign Affairs and the average female control group studied material geographyin the traditional manner in the light of these results concluded researcher efficient reading ofForeign Affairs in the achievement of students of the information as if directing them to readbooks and external sources was positive and recommended the researcher Care Library andimprove their standards and provide them with books, publications and recent publicationsthat are relevant in explaining the vocabulary of the textbook and to encourage students toread foreign and proposed studies measure the impact of readings of State in the othervariables Kalatjahat about geography or to the development of thinking deductive or or theacquisition of critical thinking concepts.